Genomic Selection in Aquaculture Breeding Programs - Mehar S. Khatkar (John Wiley & Sons Ltd., 2025)
Genome selection was initially proposed in 2001, and it has now been widely used within livestock species. Thus far its application in aquaculture species has been very limited. In this chapter, the principles of genome selection are introduced, followed by an example of how to conduct genome selection, and, at the end, some perspectives for aquaculture species are provided. Recent advances in molecular techniques have made it possible to genotype thousands of geneticmarkers (typically SNPs) even in species in which genome assemblies or genetic maps are not available.The ever-decreasing cost of genotyping and sequencing is now making it possible to use these tools in many aquaculture species.The genotypic data frompedigreed or non-pedigreed populations can provide insights into the population structure, gene association, and information for selective breeding. Indeed,with the availability of molecular data, there is no need to record pedigree information anymore, which can greatly simplify breeding schemes, especially for aquaculture species. In this chapter, the concept of genomic selection (GS) is first described—that is, the application of geneticmarkers in selective breeding schemes—and then, its potential in aquaculture breeding programs is explored.